398 CARDIAC MAGNETIC RESONANCE PHENOTYPE AND GENOTYPE IN LEFT-SIDED CARDIOMYOPATHIES: CHARACTERIZATION AND CLINICAL OUTCOMES. (15th December 2022) - Castrichini, Matteo; De Luca, Antonio; Paldino, Alessia; Cittar, Marco; Dal Ferro, Matteo; Angelis, Giulia De; Barbati, Giulia; Medo, Kristen; Groves, Daniel; Quaife, Robert; Eldemire, Ramone; Gigli, Marta; et al.
Abstract: Background: The combined prognostic role of cardiac magnetic resonance (CMR) and genotype in cardiomyopathies has not been fully investigated. The aim of this study was to identify specific genotype-CMR phenotype correlations in a well-characterized cohort of patients with a spectrum of left-sided cardiomyopathies spanning from arrhythmogenic (ACM) to dilated cardiomyopathy (DCM), and analyze patients' outcome. Methods and Results: One-hundred and seventy-four patients with DCM (127) and left sided ACM (47), who underwent a comprehensive evaluation including genetic testing and CMR imaging, were enrolled in this study. The phenotype was classified as DCM or ACM according to current consensus criteria. The primary outcome was a composite of sudden cardiac death/life-threatening ventricular arrhythmias (SCD/MVA). DCM patients showed more frequently pathogenic or likely pathogenic (P/LP) variants of non-arrhythmic genes (34% vs. 7%, p < 0.001), whereas ACM patients reported more frequently P/LP variants of arrhythmic genes (47% vs. 8%, p < 0.001) and non-ischemic free-wall LGE (30% vs. 10%, p = 0.002). After a median follow-up of 92 months (interquartile range 46 - 168), 39 patients (22%) reached the combined endpoint. Carrying a P/LP variant of arrhythmic genes (hazard ratio (HR) 2.2, 95% confidence interval (CI) 1.1 - 4.4, p = 0.024) along with presence of LGE (HR 4.5, 95% CI 1.99 - 11.5, p < 0.001) were independently associated with the study endpoint. Conclusion: In cohort of well-characterized left sided cardiomyopathies patients spanning from ACM to DCM, a P/LP variant of arrhythmic genes along with presence of LGE were independent predictors of SCD/MVA.